JPEG 2000 coding of image data over adaptive refinement grids - Gamito, M. N.; Dias, J. (SPIE 5150, Visual Communications and Image Processing 2003, 2003)
An extension of the JPEG 2000 standard is presented for non-conventional images resulting from an adaptive subdivision process. Samples, generated through adaptive subdivision, can have different sizes, depending on the amount of subdivision that was locally introduced in each region of the image. The subdivision principle allows each individual sample to be recursively subdivided into sets of four progressively smaller samples. Image datasets generated through adaptive subdivision find application in Computational Physics where simulations of natural processes are often performed over adaptive grids. It is also found that compression gains can be achieved for non-natural imagery, like text or graphics, if they first undergo an adaptive subdivision process. The representation of adaptive subdivision images is performed by first coding the subdivision structure into the JPEG 2000 bitstream, ina lossless manner, followed by the entropy-coded and quantized transform coefficients. Due to the irregular distribution of sample sizes across the image, the wavelet transform must be applied on irregular image subsets that are nested across all the resolution levels. Using the conventional JPEG 2000 coding standard, adaptive subdivision images would first have to be upsampled to the smallest sample size in order to attain a uniform resolution. The proposed method for coding adaptive subdivision images is shown to perform better than conventional JPEG 2000 for medium to high bitrates.